Technological change and skill development in Sudan - Mohamed Nour, Samia (Springer Berlin Heidelberg, 2013)
With the ongoing restructuring in Sudan, structural issues such as the need for skill development and interaction with technological change need an in-depth analysis that this book offers. The central themes of this book are- required skill formation, upskilling of the workers, and their interaction with technological change in lieu of a deficient educational system and its implications. An empirical investigation of the causes and consequences of low skill and technology indicators using a primary survey at macro and micro levels is undertaken. This is followed by an examination of the interaction between the low skill and technology indicators, the relationships between skill, upskilling and technology indicators, skills mismatch, the uses and impacts of ICT and differences at firm as well as industry level and knowledge transfer effects. A set of recommendations towards the need for implementation of consistent policies, increasing incentives and collaboration between public and private institutions completes the book.